COVID-19 PANDEMIC AND COMMODITY MARKET INSTABILITY: EVIDENCE FROM THE LONDON METAL STOCK EXCHANGE - STOJANOVIC, DRAGICA MILORAD (Poslovna ekonomija, 2021)
The paper provides insight into the behavior of non-ferrous metal prices on the London Stock Exchange during the health crisis caused by the spread of coronavirus in the period January 22 – October 30, 2020. The aim of this paper is to determine a statistically significant relationship between the number of confirmed cases of COVID-19 and non-ferrous metals prices copper, aluminum, zinc, nickel, lead and tin. A simple linear regression was used in the paper to obtain results. Following the report of the World Health Organisation and the introduction of restrictive measures to prevent the spread of coronavirus, the results of the regression support the fall in non-ferrous metals prices on the London Stock Exchange. Also, the results suggest that the measures taken to address the negative economic consequences of the health crisis are associated with rising non-ferrous metal prices. As the economic impact of the pandemic is still uncertain, through an indicative review of current impacts, the conducted research also provides an opportunity to predict the price of non-ferrous metals in the future. The assumption that price stability in the metal market depends on the degree of control of pandemic COVID-19 provide a basis for future research.
Keywords: COVID-19 pandemic, commodity market, non-ferrous metals price, simple linear regression